The practice of flash point determination: a laboratory resource - Montemayor, Rey G., 1944- (ASTM manual series, 2013)
Flash point defines petroleum product quality. This user's guide compares commonly used flash point apparatus and procedures and provides general guidance in the use and interpretation of standard ASTM flash point methods. The manual is intended for those who run the flash point tests or for the users of the results of such tests. This includes lab technicians in testing laboratories, trucking, railway, aviation, shipping and warehousing of volatile materials to determine if they get what they ordered based on the flash point and the volatility of the materials. Also for businesses that receive DOT/EPA regulated petroleum products and refinery labs. --